A statistical quality control study on Armel Plastics Company Incorporated - Gutano, Georgina; Manuel, Jelle Jasmin M.; Pendel, Vivien I.; Perez, Diane May M. (College of Engineering, 2002)
Armel Plastics Inc. is a producer of plastic containers that manufactures bottles for other companies. The group documented the quality system of the company and conducted problem analysis for a component of a major product line of the company. The data for rejection for Zonrox 8 oz. were analyzed using the Pareto Chart. The top three major causes of rejections were blackspots, out of specifications weight, and out of specifications wall thickness. These three problems were further investigated using the Ishikawa Diagram to generate possible causes. The three major causes of rejections were plotted in appropriate control charts. The weight and wall thickness were plotted in Xbar and R charts while the number of bottles with blackspots were plotted in a p-chart. The capability of the process to fabricate bottles within specifications for weight and wall was calculated by computing for the capability indices. The potential and actual capability indices were below the required 1.33 value. The actual process capability indices for the left and right were not equal as well, which denoted that the process is off-centered. The results revealed that the process is out of control and incapable of meeting the weight and wall thickness specifications of the product. Given these results, the group recommended that the company perform Design of Experiments for the factors that affect the weight and wall thickness, implement acceptance sampling for incoming raw materials and increase the frequency of cleaning of the screen of the blow molding machine. Implementation plans were provided for the design of Experiments, acceptance sampling, and frequency of cleaning of the screen.